Application of Appropriate Technology in Producing Fish Tendon Crackers with Good Quality and Safe for Consumption - Ni Made Darmadi; Dewa Nyoman Sadguna; Dewa Gede Semara Edi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
The fish tendon is fresh waste from Tuna Fish which has only been used as a fish meal. Partners process it into foodstuffs with higher economic value. However, processing fish veins into panga materials with high economic value requires the application of technology. Applied research in community service (PKM) Urat Ikan Urat Crackers aims to apply appropriate technology to partners to be able to apply in producing Fish Tendon Crackers with good quality and safe for consumption, providing knowledge about business group formation, business management, sanitation, and hygiene, packaging and marketing and helping Mintra find product PIRT numbers. The method is used through Interviewing, Counseling, Face-to-Face, and Direct Practice. With this method, it is hoped that partners will get knowledge and solutions to the problems faced. The activity was carried out in stages, the first stage, the team provided counseling, in the second stage, the Team provided direct practice regarding the manufacture of quality tuna fish tendon crackers that was safe for consumption, and carried out 3 repetitions of the practice, evaluated so that the Partners understood. The output target to be achieved in this PKM activity is to publish the results of the Activity in the Journal, disseminate and publish them in the print / electronic period media and make a video of the activity with a duration of 4 minutes.